Wonder Woman and philosophy : the Amazonian mystique - Held, Jacob M., 1977- (Hoboken, NJ : Wiley Blackwell, 2017)
Wonder Woman and Philosophy: The Amazonian Mystique explores a wide range of philosophical questions surrounding the most popular female superhero of all time, from her creation as feminist propaganda during World War II up to the first female lead in the blockbuster DC movie-franchise. -The first book dedicated to the philosophical questions raised by the complex and enduringly iconic super-heroine -Fighting fascism with feminism since 1941, considers the power of Wonder Woman as an exploration of gender identity and also that of the human condition - what limits us and what we can overcome -Confronts the ambiguities of Wonder Woman, from her roles as a feminist cause and fully empowered woman, to her objectification as sexual fantasy -Topics explored include origin stories and identity, propaganda and art, altruism and the ethics of care, Amazonians as transhumanists, eroticism and graphic novels, the crafting of a heroine, domination, relationships, the ethics of killing and torture, and many more.
Includes index.
Online resource; title from PDF title page (John Wiley, viewed March 1, 2017).
Keywords: Wonder Woman -- (Fictitious character); Wonder Woman -- (Fictitious character); Comic books, strips, etc. -- Moral and ethical aspects; Philosophy in literature; Electronic books